MASA DEPAN MASYARAKAT HINDU NUAULU DI MALUKU TENGAH - I Nyoman Yoga Segara; Kuckreja, Ravinjay (Penamas, 2024)
Fearing discrimination from the Indonesian government, the Nuaulu tribe in Central Maluku have chosen to declare themselves as “Hindu”. Their ancestral customs are similar to mainstream Hindu beliefs and traditions. However, they lack the Hindu Gods, the Sanskrit mantras and the unifying scripture of the Vedas. What is left is a local indigenous religion. However, their bad experience with being categorized as an ancestral faith (aliran kepercayaan) has led them to be self-declared Hindus. In such a circumstance, Hinduism can either unconditionally accept them despite the lack of evident resemblance, or the Nuaulu tribe can alter their religion’s façade to duplicate crucial Hindu identifiers. This paper questions what it means to be a Hindu, what Hinduization is, and how discriminatory definitions torment indigenous religions.